DIGITAL MARKETING SEBAGAI STRATEGI OPTIMALISASI PEMASARAN DAN PROMOSI DALAM REVITALISASI DAYA TAHAN UKM SEPATU MENGHADAPI PANDEMI COVID-19 DAN REVOLUSI INDUSTRI 4.0 - Sufiatul Maryana; Dini Suhartini; Yudhia Mulya; Agung Prajuhana Putra (Universitas Teknokrat Indonesia, 2022)
The shoe home industry is part of SMEs which are no less important for the national economy. Information technology plays an important role in the online transaction process or digital marketing, especially in the field of sales to small and medium businesses, this requires home entrepreneurs or SMEs to use various available applications to meet customer needs and maintain and increase income in their business sector. Before the pandemic period, the R-Four shoe business received orders in a conventional way from resellers with a large number of orders for each type of shoe and sandal, usually used for well-known brands on the market, but at the beginning of the pandemic everything changed from the order stopped, no payment has been paid and there is no more news from the reseller. As a result, this business almost went out of business because there were no transactions, the circulation of money stopped and many employees were laid off. In this condition, SME business actors need to take different steps in order to maintain the business that has been initiated, supported by a service team from Pakuan University who provides a platform for doing digital marketing and assisting the use of applications so that it becomes a promotional strategy, sales can run and continue to increase.